2017
DOI: 10.1007/s10936-017-9494-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Simple Semantics in the Process of Artificial Grammar Learning

Abstract: This study investigated the effect of semantic information on artificial grammar learning (AGL). Recursive grammars of different complexity levels (regular language, mirror language, copy language) were investigated in a series of AGL experiments. In the with-semantics condition, participants acquired semantic information prior to the AGL experiment; in the without-semantics control condition, participants did not receive semantic information. It was hypothesized that semantics would generally facilitate gramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Strengthening this possibility, de Vries et al (2012) found advantages in reaction times for nested grammars in German-speaking (nested-based language) participants when compared to Dutch ones. Further studies with German participants (Öttl et al, 2015, 2017) showed a different pattern in that nested and crossed dependencies were equally difficult to learn and process. However, Öttl and colleagues did not use an additional baseline classification test before training, thus leaving open a complete characterization of learning outcomes and subsequent considerations on the role of linguistic experience.…”
Section: Adjacent Nonadjacent Nested and Nonadjacent Crossed Dependen...mentioning
confidence: 97%
See 2 more Smart Citations
“…Strengthening this possibility, de Vries et al (2012) found advantages in reaction times for nested grammars in German-speaking (nested-based language) participants when compared to Dutch ones. Further studies with German participants (Öttl et al, 2015, 2017) showed a different pattern in that nested and crossed dependencies were equally difficult to learn and process. However, Öttl and colleagues did not use an additional baseline classification test before training, thus leaving open a complete characterization of learning outcomes and subsequent considerations on the role of linguistic experience.…”
Section: Adjacent Nonadjacent Nested and Nonadjacent Crossed Dependen...mentioning
confidence: 97%
“…Overcoming the limitations of studies with Dutch participants, we recruited Portuguese-speaking participants, who have little or no experience with crossed dependencies between different words or constituents (but please see Martins, 2006, and Piechnik, 2015, for reduplication phenomena in Portuguese). Overcoming the limitations of Öttl and colleagues’ (2015, 2017) studies with German participants (also unexperienced with crossed dependencies), we used a learning approach that included pre- and posttraining preference classification tests. If nested dependencies proved to be easier to learn than crossed ones, this would strengthen the idea that formal language hierarchy is compatible with the cognitive architecture of humans.…”
Section: Adjacent Nonadjacent Nested and Nonadjacent Crossed Dependen...mentioning
confidence: 99%
See 1 more Smart Citation